An observation of common physiological parameters during esports activity. (2020) - Koshy, Aaron; Čironis, Lukas; McVey, Matthew; Sousa, Amber; Ahmad, Sophia L.; Hassan, Tamzid; Yuen, Kyle; Douris, Peter; Zwibel, Hallie; DiFrancisco-Donoghue, Joanne
No abstract available